ANALISIS PENERAPAN ISO 9001: 2008 TERHADAP PENINGKATAN PRODUKTIVITAS DAN KINERJA KARYAWAN DI PERUSAHAAN JASA KONSTRUKSI ( STUDI KASUS PT. WIJAYA KARYA BETON TBK DI KABUPATEN MAJALENGKA ) - LUMBAN TORUAN, ERNI SARI (J-ENSITEC, 2023)
Productivity is one of the components that every company must have. For companies that utilise human resources, it is directed at increasing employee productivity and performance to the maximum. The company PT WIKA Beton Tbk in Majalengka already has an ISO 9001: 2008 certificate and has implemented the ISO 9001: 2008 quality management system as a standard for the precast concrete products it produces. The purpose of this study is to analyse the application of ISO 9001: 2008 to increase employee productivity and performance simultaneously and partially at PT.WIKA Beton Tbk in Majalengka. This study uses the statistical method of path analysis, completed using the SPSS for windows release 20.0 programme. The study results show that the direct effect of the quality management system on productivity improvement is 5.76%, the effect of resource management on productivity improvement is 1.00%, the effect of continuous improvement on productivity improvement is 40.45%, and the combined effect is 85.80%. The effect of quality management system on employee performance is 0.1521%, continuous improvement on employee performance is 77.088% and combined is 71.30%. The effect of productivity improvement on employee performance is 72.932% and the combined effect is 73%. While the indirect effect between the quality management system to increase productivity through employee performance is 24.096%, resource management to increase productivity through employee performance is 7.174% and continuous improvement to increase productivity through employee performance is 54.314%. The results show that the company pays more attention to variables that have a major influence on improving employee productivity and performance.